The Effect of the Mathematics Course Taught with Logical Reasoning Methods on the Success of Students in Skill-Based Questions and Student Opinions on Teaching - Altintas, Esra; Angay, Meltem (Mimbar Sekolah Dasar, 2023)
This research aimed to examine the effects of the mathematics course taught with logical reasoning methods on the success of students in skill-based questions and to examine students' opinions. In the study group of this research, 7th grade students and a total of 35 students, 18 of which were in the experimental group and 17 in the control group, were studied. Since qualitative and quantitative data are used together, the method of this research is mixed method research. In the results of the study, it was found that the pre-test and post-test averages of the experimental group students who were taught with logical reasoning methods differed significantly in favor of the post-test, the difference in the pre-test and post-test results of the control groups, who were taught with traditional methods, was not significant. It was observed that the post-test averages of the control and control groups differed significantly in favor of the experimental group. When the opinions of the experimental group students were examined, it was concluded that in the lessons taught using logical reasoning methods, the rules were reached by themselves, they were fun, and skill-based questions were difficult, but there was often a change in their thoughts.